Thermal runaway hazard characteristics and influencing factors of Li‐ion battery packs under high‐rate charge condition. (18th December 2019) - Bian, Huan; Wang, Zhirong; Jiang, Juncheng; Yang, Yun; Wang, Hao; Chen, Shichen
SUMMARY: In a special environment such as a high‐rate charge or discharge one, the positive and negative electrode materials of a lithium ion battery may undergo a chemical exothermic reaction with an electrolyte and a binder and release a large amount of heat to cause thermal runaway, resulting in harmful consequences. In this paper, high‐rate charging experiments of different types of 18650 Li‐ion battery packs were performed to study the behavior and influencing factors of Li‐ion battery packs when thermal runaway occurred. Automatic test equipment with battery comprehensive parameters was adopted, and a Li‐ion battery thermal runaway test device was designed and used to test a series of Li‐ion battery packs under high‐rate charging conditions. The series of tests were conducted under different conditions of different cell spacing, pick‐up point positions and connection modes. Results showed that under the above three different conditions, the initial time and the initial temperature of the thermal runaway of the Li‐ion battery packs, the maximum temperature of thermal runaway and the position where the first thermal runaway battery occurred showed some regular changes.